2006
DOI: 10.1002/ijc.22292
|View full text |Cite
|
Sign up to set email alerts
|

Expression of activation‐induced cytidine deaminase in human hepatocytes during hepatocarcinogenesis

Abstract: Activation-induced cytidine deaminase (AID) plays a role as a genome mutator in activated B cells, and inappropriate expression of AID has been implicated in the immunopathological phenotype of human B-cell malignancies. Notably, we found that the transgenic mice overexpressing AID developed lung adenocarcinoma and hepatocellular carcinoma (HCC), suggesting that ectopic expression of AID can lead to tumorigenesis in epithelial tissues as well. To examine the involvement of AID in the development of human HCC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
115
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 35 publications
3
115
0
1
Order By: Relevance
“…Consistently, several studies have reported that genetic aberrations are frequently detected in non-tumorous inflamed epithelial tissues where the risk of cancer development is remarkably high [38][39][40] . For example, TP53 mutations are detected in the inflamed mucosa of the colonic epithelium of patients with inflammatory bowel disease 41,42 .…”
Section: Discussionsupporting
confidence: 57%
“…Consistently, several studies have reported that genetic aberrations are frequently detected in non-tumorous inflamed epithelial tissues where the risk of cancer development is remarkably high [38][39][40] . For example, TP53 mutations are detected in the inflamed mucosa of the colonic epithelium of patients with inflammatory bowel disease 41,42 .…”
Section: Discussionsupporting
confidence: 57%
“…The presence of mutations in non-cancerous tissue expressing AID is reminiscent of a study on human patients with chronic hepatitis (Kou et al, 2006), together suggesting a causal role of AID in tumorigenesis. It is noteworthy that the mutations corresponding to two mutational hot spots in TP53 gene encoding human p53 (R273 and R175) were included in mutations found in TNAP-AID HCC.…”
Section: Discussionmentioning
confidence: 92%
“…We consider that the TNAP-AID mouse model is useful for human HCC studies because it has been shown that AID is induced in the human pre-cancerous conditions of chronic hepatitis and cirrhosis (Kou et al, 2006). The relatively long latency before HCC development in this model is reasonable, considering that it is a physiological recapitulation of a human tumour phenotype that takes decades to develop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that aberrant AID expression can induce SHM in a nonimmunoglobulin gene in nonlymphoid cells Yoshikawa et al, 2002), and mice with constitutive expression of AID develop various tumors, including T-cell lymphomas and lung adenomas, suggesting that AID has direct oncogenic potential via the mutagenesis of inappropriate target genes (Okazaki et al, 2003). Notably, we recently revealed that endogenous AID was significantly upregulated in both HCC and surrounding noncancerous liver tissues with underlying cirrhosis or chronic hepatitis, where only minute AID expression is detectable in normal liver (Kou et al, 2007). Moreover, both tumor and nontumor liver tissues with hepatitis C virus (HCV) infection exhibited significantly higher expression levels of the AID gene compared with liver tissues of normal control.…”
Section: Introductionmentioning
confidence: 97%